Development of Ukrainian statehood and authorities of Carpathian Ukraine - S. Yu. Ivanov (Bulletin of Kharkiv National University of Internal Affairs, 2024)
The features and prerequisites for the declaration of Carpathian Ukraine’s independence are studied, and the process of establishing state authorities under the leadership of Augustine Voloshyn is traced. The focus is placed on the difficult foreign and internal political situation of the newly created Ukrainian state, and the reasons that prompted the government of Carpathian Ukraine to abandon the development of democratic values, on the basis of which the young state was to develop, are identified.The development of the state and legal status of Zakarpattia from the period of demands for autonomy for the region to the stage of creation of an independent, self-governing state is shown in general terms. The influence of external factors on the process of state formation in Zakarpattia before the Second World War is studied, the role of Carpathian Ukraine in the development of the national statehood is analysed.Particular attention is paid to highlighting the historical and legal significance of the development of Carpathian-Ukrainian statehood, in particular, its impact on the actualisation of all-Ukrainian issues in international relations.The activities of Carpathian Ukraine's government and the process of forming its state authorities, which, in turn, went through a peculiar evolution that began when Czech Parliament adopted the Constitutional Law on 22 November 1938, which introduced a federal system for the state of Czechs, Slovaks and Ukrainians of Zakarpattia, and finished in March 1939, when Carpathian Ukraine became an independent state, are demonstrated. It is emphasised that the declaration of the Act of Independence of Carpathian Ukraine on 15 March 1939 strengthened the liberation ideas, inspiring the struggle for the independence of Ukrainians in all ethnic areas and creating the necessary international preconditions for the reunification of the region with other Ukrainian territories in the future.